White blood cell-based detection of asymptomatic scrapie infection by ex vivo assays. - Sophie Halliez (Public Library of Science (PLoS), 2014)
Prion transmission can occur by blood transfusion in human variant Creutzfeldt-Jakob disease and in experimental animal models, including sheep. Screening of blood and its derivatives for the presence of prions became therefore a major public health issue. As infectious titer in blood is reportedly low, highly sensitive and robust methods are required to detect prions in blood and blood derived products. The objectives of this study were to compare different methods--in vitro, ex vivo and in vivo assays--to detect prion infectivity in cells prepared from blood samples obtained from scrapie infected sheep at different time points of the disease. Protein misfolding cyclic amplification (PMCA) and bioassays in transgenic mice expressing the ovine prion protein were the most efficient methods to identify infected animals at any time of the disease (asymptomatic to terminally-ill stages). However scrapie cell and cerebellar organotypic slice culture assays designed to replicate ovine prions in culture also allowed detection of prion infectivity in blood cells from asymptomatic sheep. These findings confirm that white blood cells are appropriate targets for preclinical detection and introduce ex vivo tools to detect blood infectivity during the asymptomatic stage of the disease.